La enseñanza de lenguas extranjeras en los siglos XVI-XVIII. El caso del Español - Miguel A. Martín Sánchez; Charo Nevado Fuentes (Ogigia, 2009)
The teaching of foreign languages is something that has always been present in the course of history. This article analyzes the period between the XVI and XVIII centuries, since it is in that moment when modern languages reach its maximum spreading being a reason of interest and study. Throughout these pages we will analyze the evolution of language teaching from the Humanism until the Illustration paying special attention to the methodology used through this period. We will make a special mention to the case of Spanish, analyzing the spreading that had outside of our boundaries and we will stop to look at the different resources used in the learning of Spanish language as foreign language in more detail. La enseñanza de lenguas extranjeras es un tema que ha estado siempre presente a lo largo de la historia. Este artículo analiza el periodo comprendido entre los siglos XVI-XVIII, ya que es el momento en el que las lenguas modernas alcanzan su máxima difusión siendo motivo de interés y de estudio. A lo largo de estas páginas analizaremos la evolución de la enseñanza de lenguas desde el Humanismo hasta la Ilustración, reﬂexionado sobre la metodología utilizada a lo largo de este periodo. Haremos una mención especial al caso del español, analizando la difusión que tuvo fuera de nuestras fronteras y deteniéndonos en los diferentes materiales empleados en el aprendizaje del idioma español como lengua extranjera.